2018
DOI: 10.1002/nur.21882
|View full text |Cite
|
Sign up to set email alerts
|

The associations of occupational hazards and injuries with work environments and overtime for nurses in China

Abstract: Occupational hazards (OHs) and occupational injuries (OIs) may contribute to nurses needing sick time and to a high financial burden for hospitals. There is little published literature about nurse-reported OHs/OIs and their relationships with work environments and working overtime in China. This study was designed to describe Chinese hospital registered nurses' OHs/OIs and to explore the associations between work environments, working overtime, and nurse-reported OHs/OIs. This cross-sectional study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
1
24
0
1
Order By: Relevance
“…It is important to emphasize that nurses who worked voluntary overtime were found to have a higher likelihood of occupational injuries than those who did not, indicating substantial exposure to potential injuries. Several studies have also reported that working overtime significantly increased the risk of injuries in nurses (Stimpfel, Brewer, & Kovner, 2015;Unruh & Asi, 2018;Wu et al, 2018 working more voluntary overtime had higher levels of job satisfaction, but they also had higher levels of occupational injuries. Therefore, it is important to monitor both their work hours and overtime and then implement managerial strategies to prevent such occupational injuries.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to emphasize that nurses who worked voluntary overtime were found to have a higher likelihood of occupational injuries than those who did not, indicating substantial exposure to potential injuries. Several studies have also reported that working overtime significantly increased the risk of injuries in nurses (Stimpfel, Brewer, & Kovner, 2015;Unruh & Asi, 2018;Wu et al, 2018 working more voluntary overtime had higher levels of job satisfaction, but they also had higher levels of occupational injuries. Therefore, it is important to monitor both their work hours and overtime and then implement managerial strategies to prevent such occupational injuries.…”
Section: Discussionmentioning
confidence: 98%
“…Our results add evidence to the importance of building a supportive work environment for improving nurses' work attitudes. Another published article using data from this survey reported that the lowest score dimensions of work environment were "nurse staffing and resource adequacy" and "nurse participation in hospital affairs" (Wu et al, ). Thus, building a supportive work environment by allocating adequate nursing workforce and resources and enhancing nurses' role in hospital management is a potential strategy to promote nurses' positive work attitude and ultimately to stabilize the nursing workforce.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is inconclusive of the association of psychological stress with workplace accidents and injuries [10,11]. Therefore, more attention is needed to enhance the workplace safety of nurses [12].…”
Section: Introductionmentioning
confidence: 99%